The Hidden Costs of Financing a National Football League Stadium with Municipal Bonds: The Case of Allegiant Stadium in Las Vegas - Leobardo Diosdado; Marco Lam; Charlie Parrish (Journal of Applied Sports Management, 2022)
The development of professional sports stadiums in the United States typically relies on public funding in the form of municipal bonds. Prior research has identified several economic and noneconomic reasons local governments choose to direct public funds towards the construction of stadiums. The overall conclusion of this research suggests sport stadiums do not result in significant increases in economic activity and therefore subsidized stadium development projects lack economic justification. In this study, the process of issuing bonds is examined. The authors describe the bond issuance process and utilize data associated with the bonds for the development of Allegiant Stadium in Las Vegas, Nevada to quantify the hidden costs associated with financing the venue. Findings demonstrate the financial consequences for taxpayers resulting from a lack of transparency in the municipal bond issuance process.
Keywords: Stadium Finance; Asymmetric Information; Municipal Bond; Bond Underwriting